Anxiety of Blind Adolescents in Psychospiritual Perspectives - Rachmah Nur Anganthi, Nisa; Maulina, Yusri (International Journal of Psychosocial Rehabilitation, 2020)
Purpose: Blind adolescents in their special or exceptional conditions with various problems that are often faced by various problems due to difficulties in their vision function. Improving conditions that cause adolescents to be difficult. The objectives of this study (1) reduce the level of complexity of the blind using supportive therapeutic intervention methods, and (2) examine changes in perspective from an Islamic psychospiritual perspective. Methodology: Participants consisted of 6 blind adolescents from SLB-A YAAT Klaten’s students who participated in 12-24 years. Methods of data collection used observation, interviews, Focus Group Discussion (FGD), and the Taylor Manifest Anxiety Scale (TMAS) consideration scale which contained 50 questions. In addition, interviews were also conducted with key people who included guardian classes, teachers, families, and boarding mothers. Data analysis techniques using non-parametric statistical tests which include Wilcoxon technique. Results: The findings prove a decrease in the group of adolescents who experienced improvement. Thus, it can be concluded as a supportive group therapy that effectively reduces the resolution of blind adolescents.